Comparing Students’ Ability in Writing Recount Text of Grade X and Grade XI at SMAN 1 Lubuk Alung - Zikra Azkiya; Hamzah Hamzah (Universitas Negeri Padang, 2020)
This research was about the comparison between students’ ability of grade X and grade XI in writing recount text with the topic of an unforgettable experience. This study aimed to compare the level of students’ grade X and grade XI ability in writing recount text seen from the generic structure of the text. The research design of this study was descriptive research. The population of this research was all of classes grade X and grade XI of SMAN 1 Lubuk Alung. The sample was taken by using random cluster sampling technique so that the sample obtained was 1 class from grade X and 1 class from grade XI. The instrument used in this study was a test recount text for 45 minutes in at least 100 words. The students’ writing was analyzed using recount text writing rubric related to the generic structure of the text. Based on this research, students’ ability of grade XI was higher than grade X by looking from the generic structure of recount text. The ability of students grade XI was in 3 (good) category while students grade X was in 2 (weak) category. Nevertheless, there were several parts of the text that students could not understand yet how to write them.